Evaluation of Osteogenic Potentials of Titanium Dioxide Nanoparticles with Different Sizes and Shapes. (11th November 2020) - Ren, Yixing; Feng, Xinxing; Lang, Xinhua; Wang, Jianbo; Du, Zhipo; Niu, Xufeng
Abstract : TiO2 nanoparticles (NPs) have the potential to be used in the human body as an artificial implant because of their special physicochemical properties. However, information about the effects of TiO2 NPs on preosteoblast proliferation and osteogenic differentiation is not clear. In this work, we focus on the impact of TiO2 NPs with different shapes and sizes on the proliferation and differentiation of MC3T3-E1 cells. The morphology and physicochemical properties of TiO2 NPs are analyzed by scanning electron microscopy, transmission electron microscopy, Quadrasorb SI analyzer, dynamic light scattering, and zeta potential. The MTT results indicate that when the concentration of TiO2 NPs is less than 20 μ g/mL, the proliferation of osteoblasts is preserved the most. The expression of alkaline phosphatase and osteocalcin is detected by BCA and enzyme-linked immunosorbent assay to analyze the differentiation of osteoblasts. The results indicate that both rutile and anatase TiO2 NPs have a significant inhibiting influence on the differentiation of osteoblasts. Alizarin Red staining is performed on cells to detect the mineralized nodules. The results show that TiO2 NPs can promote the mineralization of MC3T3-E1 cells. Then, we study the oxidative stress response of MC3T3-E1 cells by flow cytometry analysis, and all TiO2 NPs induce the excessive generation of reactive oxide species. On the other hand, our study also shows that the early apoptotic cells increase significantly. TiO2 NPs are swallowed by cells, and then the agglomerated particles enter mitochondria, causing the shape of mitochondria to change and vacuolation to appear. All these results show that TiO2 NPs have certain cytotoxicity to cells, but they also promote the mineralization and maturation of osteoblasts.